A nitrogen transformation model for multi-layer enhanced groundwater remediation technology. Issue 22 (17th November 2018) - Yang, Yu; Ma, Zhifei; Jiang, Yonghai; Lian, Xinying; Xi, Beidou; Pei, Yu
ABSTRACT: The multi-layer enhanced groundwater remediation technology (MET) is an innovative platform that integrates physical chemistry, bioremediation, and phytoremediation technology to safely and effectively remediate ammonia nitrogen in groundwater. A nitrogen transformation model was established to study the mechanism of nitrogen transformation within ammonia nitrogen removal in the MET. The model considered organic nitrogen, ammonia nitrogen, and nitrate nitrogen as the variables, and ammonification, nitrification, denitrification, microbial assimilation, plant absorption, adsorption–desorption, and volatilization as the influencing factors. The unknown parameters of the model were obtained by fitting the data from a bench-scale experiment, and the results of the model validation and comparison showed that under the experimental initial conditions (the hydraulic load of the influent is 14.68 m 3 /(m 2 d) and the concentration of the ammonia nitrogen is 25.0 mg/L) and after the device ran for 45d continuously, the simulated and measured average concentration values of ammonia nitrogen in the effluent were 1.701 mg/L and 1.775 m/L, respectively, and the relative deviation was 4.17%. The simulated and measured average concentration values of nitrate nitrogen in effluent were 11.474 mg/L and 11.244 m/L, respectively, and the relative deviation was 2.05%, and the total removal rate was 92.07%. Thus it can be seen that the predicted values of the nitrogen transformation model were in good agreement with the measured values, and the model could be applied to forecast the long-term remediation effects of nitrogen in groundwater by MET.